Further arrangement of as built drawing & related documents for constructed piles & D-wall of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding further arrangement of as built drawing & related documents for constructed piles & D-wall of BRAC university new campus project.